Case Report: Hepatopulmonary syndrome as the first clinical manifestation of cirrhosis in a patient with underlying chronic lung disease - Murphy, Charles (F1000Res, 2019)
An 86 year old woman with multiple chronic lung diseases (including chronic obstructive pulmonary disease, bronchiectasis, and untreated mycobacterium avium-intracellulare) presented with two weeks of increased shortness of breath, notably worse when seated as compared to when lying down. After treatments focused on her known conditions did not resolve her dyspnea, the differential diagnosis was broadened and she was found to have evidence of cirrhosis on imaging. As a result of this new diagnosis, transthoracic echocardiography and arterial blood gas analysis were performed and together yielded the diagnosis of hepatopulmonary syndrome. We describe a rare presentation of hepatopulmonary syndrome manifesting as a patient’s first clinical evidence of suspected cirrhosis, a diagnosis made difficult by this patient’s numerous other lung diseases which muddied the picture.